(3UahI GdReGf ajef Jhdi Ydi eUQ ef CejQ hSdWGfs - (3GdbdYGhj , eUWaj Hf eMeO Hf jhSa GdUahj,J (B1230 (3g` s
(3ChdgG (B:s
(3fMeOc jG ef JaQO HGdHbGA hGdOhGe s
(3BNQgG (B:s
(3hai jhe GdSHJ NGeS YTQjf QHjY GdChd SfI KdGK hYTQheGFJjf hCda , MVQ Sdje Hc GdePchQ Edi eUQ ,hCJe GdUdM Hjf GdHGTG hGdCeQGA GdeUQjjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B241 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B285s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B92 s
(3eUOQ GbJfGA GdCUd (B:s
(3ShgGL (B((3JGQjN (B51) s
Keywords: (3GdJGQjNs